Deep Sea Drilling Program Site 10-95 benthic foraminifera stable isotope, grain size and X-ray fluorescence data across Eocene/Oligocene Boundary, southern Gulf of Mexico - Standring, Patricia; Lowery, Christopher M; Martindale, Rowan C (PANGAEA, 2025)
This dataset contains analysis of Deep Sea Drilling Program Site 95 sediment cores from the southeastern Gulf of Mexico from the late Eocene to the early Oligocene. The data include benthic foraminifera population counts of 300 individuals from each sample where possible; however, most samples did not yield 300 individuals. From these population counts, there are calculated Fisher-α diversity and Shannon Diversity Index values. The data set also includes stable carbon (δ13C) and oxygen (δ18O) isotope data from benthic foraminifera species Nuttallides truempyi, Oridorsalis umbonatus, and Cibicidoides spp. Isotope values are corrected to Cibicidoides spp. according to Katz et al. (2003). The dataset provides corrected and uncorrected values for N. truempyi and O. umbonatus. Stable isotopes were measured on a Gasbench II coupled to a Thermo MAT253 isotope ratio mass spectrometer in the Stable Isotope Laboratory at the University of Texas at Austin and reported VPDB. Additional data are grain size measurements acquired from a laser grain size analyzer (Malvern Mastersizer 3000), and X-Ray Fluorescence (XRF) data acquired on the third-generation XRF scanner at the Gulf Coast Repository at Texas A&M University. XRF data were measured at ~5 cm resolution at 10kv and 30kV and quality controlled by removing data with positive Ar values, which indicate air was measured rather than the sediment core surface.
Keywords: Benthic foraminifera; Benthic foraminifera assemblages; benthic foraminifera isotopes; Eocene-Oligocene Transition; Paleoceanography; XRF data